Sertoli Cells Dictate Spermatogonial Stem Cell Niches in the Mouse Testis - Oatley, M. J.; Racicot, K. E.; Oatley, J. M. (Biology of reproduction, 2011)
Sustained spermatogenesis in adult males relies on the activity of spermatogonial stem cells (SSCs). In general, tissue-specific stem cell populations such as SSCs are influenced by contributions of support cells that form niche microenvironments. Previous studies have provided indirect evidence that several somatic cell populations and the interstitial vasculature influence SSC functions, but an individual orchestrator of niches has not been described. In this study, functional transplantation of SSCs, in combination with experimental alteration of Sertoli cell content by polythiouracil (PTU)-induced transient hypothyroidism, was used to explore the relationship of Sertoli cells with SSCs in testes of adult mice. Transplantation of SSCs from PTU-treated donor mice into seminiferous tubules of normal recipient mice revealed a greater than 3-fold increase in SSCs compared to those from testes of non-PTU-treated donors. In addition, use of PTU-treated mice as recipients for transplantation of SSCs from normal donors revealed a greater than 3-fold increase of accessible niches compared to those of testes of non-PTU treated recipient mice with normal numbers of Sertoli cells. Importantly, the area of seminiferous tubules bordered by interstitial tissue and percentage of seminiferous tubules associated with blood vessels was found to be no different in testes of PTU-treated mice compared to controls, indicating that neither the vasculature nor interstitial support cell populations influenced the alteration of niche number. Collectively, these results provide direct evidence that Sertoli cells are the key somatic cell population dictating the number of SSCs and niches in mammalian testes.